Role of microencapsulated Lactobacillus plantarum in alleviating intestinal inflammatory damage through promoting epithelial proliferation and differentiation in layer chicks - Yaoming Cui; Peiyu Huang; Haitao Duan; Shijia Song; Liping Gan; Zhen Liu; Qiaohan Lin; Jinrong Wang; Gunghai Qi; Junjun Guan (Frontiers in Microbiology, 2023)
The alleviating effects of Lactobacillus plantarum in microencapsulation (LPM) on lipopolysaccharide (LPS)-induced intestinal inflammatory injury were investigated in layer chicks. A total of 252 healthy Hy-Line Brown layer chicks were randomly divided into six groups. Birds were injected with saline or LPS except for the control, and the diets of birds subjected to LPS were supplemented with nothing, L. plantarum, LPM, and wall material of LPM, respectively. The viable counts of LPM reached 109 CFU/g, and the supplemental levels of L. plantarum, LPM, and WM were 0.02 g (109 CFU), 1.0 g, and 0.98 g, per kilogram feed, respectively. LPS administration caused intestinal damage in layer chicks, evidenced by increased proinflammatory factors accompanied by poor intestinal development and morphology (p < 0.05). LPM/LPS significantly increased body weight, small intestine weight and length, villus height, villus height/crypt depth, and mRNA relative expression of tight junction protein genes (p < 0.05) and performed better than free L. plantarum. These findings could be attributed to the significant increase in viable counts of L. plantarum in the small intestine (p < 0.05), as well as the enhanced levels of Actinobacteriota, Lactobacillaceae, and Lactobacillus in intestinal microbiota (p < 0.05). Such results could further significantly increase goblet and PCNA+ cell percentage (p < 0.05); the mRNA relative expressions of epithelial cell, fast-cycling stem cell, quiescent stem cell, endocrine cell, and Paneth cell; and goblet and proliferative cell marker genes, including E-cadherin, Lgr-5, Bmi-1, ChA, Lysozome, Mucin-2, and PCNA (p < 0.05). Furthermore, the mRNA relative expressions of key genes involved in epithelial cell proliferation, namely, c-Myc, Cyclin-1, Wnt-3, Lrp-5, and Olfm-4, exhibited significant upregulation compared with the LPS treatment, as well as the differentiating genes Notch-1 and Hes-1 (p < 0.05). To sum up, microencapsulated L. plantarum supplementation could alleviate intestinal injury in layer chicks induced by LPS by promoting the proliferation and differentiation of intestinal epithelial cells, which could be attributed to the increase in viable count of L. plantarum in the gut and optimization in intestinal microbial flora.